2019
DOI: 10.1111/gcb.14710
|View full text |Cite
|
Sign up to set email alerts
|

Linking drought legacy effects across scales: From leaves to tree rings to ecosystems

Abstract: Severe drought can cause lagged effects on tree physiology that negatively impact forest functioning for years. These “drought legacy effects” have been widely documented in tree‐ring records and could have important implications for our understanding of broader scale forest carbon cycling. However, legacy effects in tree‐ring increments may be decoupled from ecosystem fluxes due to (a) postdrought alterations in carbon allocation patterns; (b) temporal asynchrony between radial growth and carbon uptake; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 92 publications
(191 reference statements)
8
155
1
Order By: Relevance
“…Regardless of the relative importance of active or passive components of NSC dynamics, in the context of more frequent drought, NSC is likely to eventually become limiting. This is consistent with recent work in some deciduous species showing allocation to canopy and leaf‐level photosynthesis is upregulated in the year after drought (Kannenberg et al, ), suggesting prioritization of carbon uptake following drought. Thus, on the timescales of interest here (multiple years), depletion (Adams et al, ) or loss of access to (Sala & Hoch, ) to NSC pools is likely most relevant to how NSC dynamics contribute to drought legacies, though sink limitation may play a minor role in NW trees (see below).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regardless of the relative importance of active or passive components of NSC dynamics, in the context of more frequent drought, NSC is likely to eventually become limiting. This is consistent with recent work in some deciduous species showing allocation to canopy and leaf‐level photosynthesis is upregulated in the year after drought (Kannenberg et al, ), suggesting prioritization of carbon uptake following drought. Thus, on the timescales of interest here (multiple years), depletion (Adams et al, ) or loss of access to (Sala & Hoch, ) to NSC pools is likely most relevant to how NSC dynamics contribute to drought legacies, though sink limitation may play a minor role in NW trees (see below).…”
Section: Discussionsupporting
confidence: 92%
“…showing allocation to canopy and leaf-level photosynthesis is upregulated in the year after drought (Kannenberg et al, 2019), suggesting prioritization of carbon uptake following drought. Thus, on the timescales of interest here (multiple years), depletion (Adams et al, 2017) or loss of access to (Sala & Hoch, 2009) to NSC pools is likely most relevant to how NSC dynamics contribute to drought legacies, though sink limitation may play a minor role in NW trees (see below).…”
Section: Impacts Of Compounded Droughtmentioning
confidence: 99%
“…Our model simulated extreme years to cause substantial decreases in forest NPP along the Swiss elevational and bioclimatic gradient, which is in line with previous studies that assessed the impact of climate extremes on forest productivity during extremely warm-dry years (Kannenberg et al, 2019;Vitali, Büntgen, & Bauhus, 2017;Vitasse et al, 2019). Additionally, our study highlights the importance of accounting for both extreme cold and/or wet years.…”
Section: Simulations Of Npp At the Country Scalesupporting
confidence: 87%
“…Because of increasing frequency and intensity of warm-dry events due to climate change, our results suggest that P. abies and F. sylvatica will show a substantial reduction in NPP at the lower elevational band, up to 800 m a.s.l. This effect is exacerbated by the fact that the drought response along climatic gradients will likely be altered in a nonlinear way (Kannenberg et al, 2019). However, the impact of drought on tree performance and forest productivity strongly depends on its seasonal timing (Crimmins, Crimmins, Gerst, Rosemartin, & Weltzin, 2017;Vicente-Serrano et al, 2013), calling for more research on intra-annual tree growth and climate sensitivity.…”
Section: Simulations Of Npp At the Country Scalementioning
confidence: 99%
“…A previous study has revealed that the grain loss induced by droughts has contributed about 7% of the total reduction of the global grain yield (Lesk et al, 2016). During a drought, plants can survive by closing their stomata, stabilizing intracellular water potential, and reducing the rate of autotrophic respiration, which can remarkably decrease the gross primary production (e.g., Mk et al, 2011;Doughty et al, 2015;Su et al, 2018;Kannenberg et al, 2019). There are wide-range differences among the responses of the plant growth to droughts for different ecosystems and at different spatial-temporal scales.…”
Section: Introductionmentioning
confidence: 99%